Pengaruh Lingkungan Belajar Terhadap Karakter Sosial Berbasis Sila Kedua Pancasila Pada Siswa Kelas Atas Sekolah Dasar - Ika Devi Alviana; Elpri Darta Putra (Jayapangus Press, 2026)
Social character problems among elementary school students, such as low tolerance, lack of empathy, and unfair behavior in interaction, indicate that the internalization of Pancasila values, particularly the second precept, has not been optimal, whereas the learning environment is theoretically a strategic factor in character building. This study aims to examine the effect of the learning environment on students' social character based on the second precept of Pancasila in the upper grades of SDN 58 Pekanbaru. A quantitative approach with an associative design was used, involving 70 students of grades IV, V, and VI selected through saturated sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed through descriptive statistics, prerequisite tests, and simple linear regression. The results show that the learning environment has a positive and statistically significant effect on students' social character (t = 23.188; p < 0.001), with a coefficient of determination (R Square) of 0.888, indicating that the learning environment statistically accounts for 88.8% of the variance in students' social character scores within this model. These findings suggest that a conducive physical and social learning environment is associated with stronger social character among students, particularly in empathy, social care, and fairness as reflections of the second precept of Pancasila. As the design is associative and based on single-time questionnaires, the findings reflect a statistical relationship rather than an experimental causal effect.